TRANSFORMASI IDENTITAS SEKSUAL PASCA- ISTEREKTOMI PERSPEKTIF AL-QUR'AN - Sugeng Sejati; Al Fauzan Amin; Toha Andiko (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
Hysterectomy is a surgical procedure that has a significant impact on a woman's sexual identity, not only physically, but also psychologically and spiritually. The loss of the uterus is often interpreted as a partial loss of female identity, which then triggers a crisis of self-image, feelings of loss, anxiety, and even deep depression. This study aims to explore the transformation of women's sexual identity post-hysterectomy through in-depth analysis based on scientific literature and from the perspective of Qur'anic teachings. Problem solving is done through qualitative methods based on the study of relevant and current literature. The results show that accepting bodily changes as part of fate and divine will is a key factor in the healing and recovery. Ongoing spiritual support and social support from the immediate environment significantly influenced women's identity and emotional balance recovery. Therefore, a holistic and integrative approach that includes medical, psychological, social, and spiritual dimensions is needed in post-hysterectomy assistance. This approach can help women rediscover the meaning of life and the integrity of their identity within the framework of Islamic values.